2021
DOI: 10.5935/0004-2749.20210053
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico e eletrorretinográfico de 27 pacientes com doença de Stargardt atendidos em um hospital do Brasil

Abstract: Stargardt disease is the most common type of juvenile-onset macular dystrophy. It is bilateral and symmetrical in appearance, affects the macula, and its main characteristic is the loss of central vision that starts in the first or second decade of life. The purpose of this study was to describe the profile of the patients evaluated at the Complexo Hospital de Clínicas da Universidade Federal do Paraná, as well as describe the electroretinographic findings with the full-field electroretinogram in these patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The average interval between the onset of RP symptoms and the fundoscopic diagnosis was ten years. Such delayed diagnoses have been observed for other retinal conditions in Brazilian studies [31,32]. Late referral to the ophthalmology specialist is one hypothesis for explaining the matter; however, Oliveira and Arieta studied the flow of care in ophthalmology in the Campinas region and found that the waiting time for ophthalmology consultation is between 30 and 60 days, indicating that delay in ophthalmologist referral might not be the cause for such a long gap in RP diagnosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…The average interval between the onset of RP symptoms and the fundoscopic diagnosis was ten years. Such delayed diagnoses have been observed for other retinal conditions in Brazilian studies [31,32]. Late referral to the ophthalmology specialist is one hypothesis for explaining the matter; however, Oliveira and Arieta studied the flow of care in ophthalmology in the Campinas region and found that the waiting time for ophthalmology consultation is between 30 and 60 days, indicating that delay in ophthalmologist referral might not be the cause for such a long gap in RP diagnosis [33].…”
Section: Discussionmentioning
confidence: 99%